The narrative experience in listening spaces as an enhancer of the process for adolescent autonomy within the scope of practice in mental health Primary Care (Research, Society and Development, 2024)
This article is the result of research carried out in the context of primary care in the city of Osasco with adolescents seeking mental health services with various complaints, such as self-mutilation, depression, anxiety, isolation, among others. From the mental health reception, group therapeutic care is proposed. During the sessions, teenagers are encouraged to make oral constructions of their life stories, experiences and specific moments of suffering. Besides reflecting on their vocabulary and organization of speech, they have the experience of being listened to and of listening to other teenagers with their own stories and sufferings. The applied methodology belongs to the field of qualitative approach and used semi-structured interviews. Four teenagers who already participated in the group offered by mental health professionals in primary care accepted to tell their life stories in individual interviews. From these narratives, it was possible to survey and discuss important topics, revealing the power of narratives in the process of autonomy and mental health. When analyzing the narratives produced, the influence of issues of gender, religiosity and medicalization can be observed. Such topics were compared with the literature, revealing the consonance of these findings with the referenced research. Thus, the objective of this research was to analyze how the experience of telling your story can contribute to health education and user autonomy, in a reflection in relation to mental health care for adolescents in primary care under the principle of comprehensiveness and promotion of health, from a perspective of humanization of care.